microRNA-140 Inhibits Inflammation and Stimulates Chondrogenesis in a Model of Interleukin 1β-induced Osteoarthritis - Tommy A Karlsen; Gustavo Antonio de Souza; Bjørn Ødegaard; Lars Engebretsen; Jan E Brinchmann (Elsevier, 2016)
Osteoarthritis is a serious disease of articular cartilage. The pathogenic factors contributing to this disorder are inflammation, extracellular matrix degradation and failure to rebuild the articular cartilage. Preclinical studies suggest that microRNA-140 may play a protective role in osteoarthritis development, but little is known about the mechanism by which this occurs. Here we present the results of forced expression of microRNA-140 in an in vitro model of osteoarthritis, evaluated by global proteomics analysis. We show that inflammation was reduced through the altered levels of multiple proteins involved in the nuclear factor of kappa light polypeptide gene enhancer in B-cells 1 pathway. microRNA-140 upregulated many of the components involved in the synthesis of hyaline extracellular matrix and reduced the levels of aggrecanases and syndecan 4, thus potentially both increasing cartilage repair and reducing cartilage breakdown. These results show how forced expression of microRNA-140 is likely to counteract all three pathogenic processes, and support the idea that intra-articular injection of microRNA-140 may benefit patients suffering from early osteoarthritis.